Peroxovanadic based core-shell bifunctional poly(ionic liquid)s catalyst CuO/SiO2@V-PIL: Its in-situ free radical initiation mechanism for air oxidative desulfurization. (15th February 2022) - Li, Ao; Song, Hongyan; Meng, Hong; Lu, Yingzhou; Li, Chunxi
Graphical abstract: Highlights: In-situ radical initiation is realized in the interface of core and shell. Core-shell structure shortens the radical initiation period from 90 min to 40 min. In-situ radical initiation can improve the reaction selectivity and controllability. In-situ radical initiation function can be well kept after 5 recycled uses. Abstract: Air oxidative desulfurization (ODS) is a green technology, and its catalytic activation or upgrading is necessary. Herein, air ODS performance is greatly enhanced through in-situ radical initiation on the interface of peroxovanadic based catalyst CuO/SiO2 @V-PIL. The core-shell structure shortens the radical initiation period from 90 min to 40 min, and over 99.9% of desulfurization ratio, 91.5 % of cumene conversion, and 82.8% of cumene hydroperoxide (CHP) selectivity can be retained after 5 recycled uses. On the core-shell interface, V(O)2 is decomposed into oxygen radicals, which in-situ initiate formation of CHP using O2 outside the CuO, and is regenerated by the resultant CHP. Further, different alkylbenzenes in real diesel can be directly used as substituents of cumene. The present ODS process is perspective for industrial application, and the in-situ radical initiation mechanism may be applicable for oxidative removal of other heteroatom organic pollutants.